ANALISIS PENERAPAN GREEN BUILDING MENGGUNAKAN STANDAR EXISTING BUILDING VERSI 1.1 PADA BANGUNAN GEDUNG SMKN 4 SUKOHARJO - Sukatiman, Sukatiman; Hilda Nurlaela, Febriyanti; Abdul Haris, Setiawan (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
The application of green building principles is increasingly important in efforts to create a sustainable and environmentally friendly built environment. Schools are public facilities that have a strategic role in supporting sustainable development. Greenship Existing Building version 1.1 developed by the Green Building Council Indonesia provides a standard assessment for existing buildings in order to endanger their operational continuity. This study aims to assess the application of green building principles, especially in the aspect of Appropriate Site Development (ASD) based on the Greenship Existing Building version 1.1 standard. The approach used is qualitative and evaluative, with data collected through interviews, documentation, and observation. The results of the study indicate that State Vocational High School 4 Sukoharjo has implemented 11 of the 16 assessments (Appropriate Site Development/ASD) with the category of "quite good." The main aspects implemented include: (1) community accessibility (score: 1/3) with more than five public facilities; (2) reduction of motorized vehicles (1/2) through parking rates; (3) site landscape (2/3) with local and productive plants; (4) heat island effect (2/2) with albedo values ​​of 0.35 (roof) and 0.32 (non-roof); (5) rainwater management (2/2) with runoff reduction of up to 76.5%; (6) site management (1/2) with pest control (Standard Operating Procedure/SOP); and (7) building environment (2/2) with private green open spaces and community initiatives.